Determinants of Wasting Among Children Aged 6–23 Months in Indonesia - R. Trikoriyanto E. Koritelu; Ahmad Syauqy; Ani Margawati (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Wasting is a form of malnutrition that is a significant concern globally, including in Indonesia. It has a detrimental impact on children's health, the quality of human resources, and a country's overall development. This study aims to examine the prevalence and risk factors associated with wasting in children aged 6–23 months in Indonesia. The study design is cross-sectional, utilizing secondary data from the 2022 Indonesian Nutrition Status Survey. Data collection was conducted throughout Indonesia between March and December 2022. The sample size for this study was 70,414 children aged between 6 and 23 months. Bivariate analysis (χ2 test) was employed to determine the relationship between dependent and independent variables. Furthermore, multivariate analysis utilized logistic binary regression tests to ascertain the adjusted odd ratio (aOR) risk value. The results of this study indicate that the prevalence of children aged 6–23 months in Indonesia is 7.63%, with wasting. The following factors have been identified as being at high risk of wasting: boys, children aged 12-23 months, birth weight <2500 grams, birth length <48 cm, history of exclusive breastfeeding, consumption of empty calorie drinks, history of infectious diseases, inappropriate/complete immunizations, lack of use of health services, inappropriate drinking water sources and very poor family status. Wasting is associated with several factors. Consequently, identifying these factors is of significant importance in the context of intervention efforts to prevent and address malnutrition, including wasting, in Indonesia.